Adolescence to Adulthood, Managing The Key Transitions in Developing Cyclist`s Sporting Careers: The Athlete`s Perspective - Blanchfield, J.; Yelverton, S.; McArdle, J.; Haughey, T. (Journal of Science and Cycling, 2022)
The move from youth to senior competition has been shown to be one of the most difficult transitions in an athlete`s sporting career. It has been highlighted that during this transition athletes face two typical outcomes; (i) stagnation in performance, and therefore a move back to participation or dropout, or (ii) which occurs less-frequently, a continuation in their sport to senior level (Stambulova, 2009).